2004
DOI: 10.1073/pnas.0404768101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key phosphorylation sites in the circadian clock protein KaiC by crystallographic and mutagenetic analyses

Abstract: In cyanobacteria, KaiC is an essential hexameric clock protein that forms the core of a circadian protein complex. KaiC can be phosphorylated, and the ratio of phospho-KaiC to non-phospho-KaiC is correlated with circadian period. Structural analyses of KaiC crystals identify three potential phosphorylation sites within a 10-Å radius of the ATP binding regions that are at the T432, S431, and T426 residues in the KaiCII domains. When these residues are mutated by alanine substitution singly or in combination, Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(197 citation statements)
references
References 27 publications
5
192
0
Order By: Relevance
“…KaiC exhibits autokinase and autophosphatase activity, and it assembles with KaiA and KaiB into higher oligomeric complexes with distinct activities (Nishiwaki et al 2000;Kageyama et al 2003;Kitayama et al 2003;Xu et al 2003;Nakajima et al 2005;Tomita et al 2005). The phosphorylation status of KaiC oscillates in circadian fashion (Nishiwaki et al 2004;Xu et al 2004). Key phosphorylation sites have been identified that are essential for circadian rhythmicity (Xu et al 2004).…”
Section: The Circadian Clock Of Cyanobacteriamentioning
confidence: 99%
“…KaiC exhibits autokinase and autophosphatase activity, and it assembles with KaiA and KaiB into higher oligomeric complexes with distinct activities (Nishiwaki et al 2000;Kageyama et al 2003;Kitayama et al 2003;Xu et al 2003;Nakajima et al 2005;Tomita et al 2005). The phosphorylation status of KaiC oscillates in circadian fashion (Nishiwaki et al 2004;Xu et al 2004). Key phosphorylation sites have been identified that are essential for circadian rhythmicity (Xu et al 2004).…”
Section: The Circadian Clock Of Cyanobacteriamentioning
confidence: 99%
“…Previously, we identified two phosphorylation sites in KaiC at serine 431 (S431) and threonine 432 (T432), both of which are required for rhythm generation in vivo (Nishiwaki et al 2004;Xu et al 2004). To individually examine the phosphorylation states of S431 and T432, we employed nanoflow-liquid chromatography coupled with electrospray ionization-mass spectrometry and improved SDS-PAGE (Fig.…”
Section: A Sequential Program Of Kaic Phosphorylationmentioning
confidence: 99%
“…The beautiful simplicity of this test tube oscillator demonstrates the importance of the Kai-based posttranslational timing circuit and, along with promoter-replacement experiments in vivo, dismisses the requirement for the transcriptional/translational regulatory feedback loop in the cyanobacterial system. KaiC forms an ATP-dependent homohexamer and autophosphorylates at adjacent serine and threonine residues Xu et al 2004). The phosphorylation state of KaiC fluctuates in a circadian manner in vivo, yet this progressive phosphorylation of KaiC does not appear to lead to its rapid degradation (Iwasaki et al 2002).…”
Section: Synechococcus Elongatusmentioning
confidence: 99%